2022
DOI: 10.1109/jtehm.2022.3171078
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Based Cyber-Physical System for Severity Classification of Chikungunya Disease

Abstract: Background: Artificial intelligence techniques are widely used in solving medical problems. Recently, researchers have used various deep learning techniques for the severity classification of Chikungunya disease. But these techniques suffer from overfitting and hyper-parameters tuning problems. Methods: In this paper, an artificial intelligence-based cyber-physical system (CPS) is proposed for the severity classification of Chikungunya disease. In CPS system, the physical components are integrated with computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…While absolute values for accuracy & precision were available, other metrics like delay, complexity and scalability were evaluated in terms of fuzzy range sets of Low (L), Medium, High (H), and Very High (VH), which were decided based on their internal configurations and performance across different scenarios. Based on this strategy, table 1 showcases parameters for these models, Based on this analysis, it can be observed that DF [43], TPA GAN [4], PCA NET [17], THS GAN [50], SSDP [24], MA Net [30], TSA CNN [26], and RL [42] showcase high accuracy, while DLN [40], Fuzzy GBDT [22], PD Res Net [21], GERF [39], PC SVM [41], SSDP [24], SALL [25], THS GAN [50], ACGA [23], TSA CNN [26], and RL [42] showcase high precision, which makes them useful for a wide variety of real-time clinical use cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While absolute values for accuracy & precision were available, other metrics like delay, complexity and scalability were evaluated in terms of fuzzy range sets of Low (L), Medium, High (H), and Very High (VH), which were decided based on their internal configurations and performance across different scenarios. Based on this strategy, table 1 showcases parameters for these models, Based on this analysis, it can be observed that DF [43], TPA GAN [4], PCA NET [17], THS GAN [50], SSDP [24], MA Net [30], TSA CNN [26], and RL [42] showcase high accuracy, while DLN [40], Fuzzy GBDT [22], PD Res Net [21], GERF [39], PC SVM [41], SSDP [24], SALL [25], THS GAN [50], ACGA [23], TSA CNN [26], and RL [42] showcase high precision, which makes them useful for a wide variety of real-time clinical use cases.…”
Section: Discussionmentioning
confidence: 99%
“…Their suggested model performs with 95.51% accuracy, 94.44% precision, 96.59% recall, 94.44% specificity, and an F1-score of 95.51% on the clinical gait dataset. According to [22], heart disease has a detrimental influence on people's lives since it often results in hospitalizations and fatalities. Early diagnosis and treatment depend on accurate prognosis.…”
Section: In-depth Review Of Different Models For Identification Of Hu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advances, problems such as the requirement for huge, annotated datasets, ethical considerations, and regulatory frameworks must be addressed to assure the responsible and ethical deployment of AI-driven biomedical imaging systems [3]. Collaboration among researchers, healthcare professionals, and politicians is critical to navigating these hurdles and promoting wider acceptance of innovative technologies.…”
mentioning
confidence: 99%